Facets of Facebook : use and users - Knautz, Kathrin; Baran, Katsiaryna S. (Berlin ; Boston : De Gruyter, 2016)
This collected volume gathers a broad spectrum of social science and information science articles about Facebook. It looks into facets of u sers, such as age, sex, and culture, and into facets of use, e.g. priva cy behavior after the Snowden affair, unfriending on Facebook, or Faceb ook addiction, as well as into quality perceptions. Written by leading scholars investigating the impact of Web 2.0., this volume is highly re levant for social media researchers, information scientists, and social scientists, and, not least, for everyone interested in Facebook-relate d topics.
Frontmatter -- Preface -- Contents -- Chapter 1. Unfriendin g and Becoming Unfriended on Facebook -- Chapter 2. Photo Publicatio n Behavior of Adolescents on Facebook -- Chapter 3. Does Facebook Ca use Addiction? An Analysis of German Facebook Users -- Chapter 4. Fa cebook Social Games -- Chapter 5. Information Literacy Levels of Fac ebook Users -- Chapter 6. Privacy in Social Networks After the Globa l Surveillance Disclosures -- Chapter 7. From Cooperation to Compass ion: Death and Bereavement on Social Networking Websites -- Chapter 8. Facebook: A Source for Microhistory? -- Chapter 9. Social Media a s Channels for the Public Communication of Science: The Case of Spanish Research Centers and Public Universities -- t
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (pub lisher's Web site, viewed Sep. 08, 2016)
Keywords: Facebook (Electronic resource); Online social networks; Internet users